PERFORMANCE MEASUREMENT USING VALUE FOR MONEY OF GOVERNANCE IN INDONESIA - Haliah Haliah; Matrik Irma Rante; Kusumawati Kusumawati (Advances In Social Humanities Research, 2023)
Value for Money is a method of measuring public sector performance based on three main elements, namely economy, efficiency, and effectiveness. The purpose of this activity is to measure the success of Value for Money performance (economy, efficiency, and effectiveness) in the Regional Secretariat's infrastructure and facilities improvement program. The type of activity carried out is a case study on the Regional Secretariat of the Regency. The analysis technique used is descriptive quantitative, a technique based on calculations. The measurement starts with first measuring the economy, efficiency, and effectiveness of each activity in the apparatus facilities and infrastructure improvement program, and second determining the final value of each activity. Based on the results and description of the activities, it can be concluded that the performance of the apparatus facilities and infrastructure improvement program at the Regional Secretariat of the Regency obtained a successful predicate in the Value for Money performance measurement.